PEMILIHAN UMUM DAN PEMBERANTASAN KORUPSI - Andhika Yuli Rimbawan (Legal Standing : Jurnal Ilmu Hukum, 2019)
Elections in Indonesia since independence until now have experienced many  changes and dynamics, starting from the existence of guided democracy, Pancasila democracy, to the emergence of reforms showing how dominant the role (government) of the State is in giving color to the democratic system in Indonesia. Various electoral systems have implications for increasing state officials involved in corruption. The correlation between the electoral system and the eradication of corruption is closely related, because the stages and processes that are passed by the participants of this election require very high funding. Corruption that occurs is inseparable from the influence of factors, namely corruption by greed, corruption by need, corruption by opportunities, corruption by Exposus. Efforts to eradicate corruption have been carried out with various efforts and instruments of legislation, but there are still many regional officials involved in corruption, it needs improvement through political education for the community, an information center on election participants, professional and neutral law enforcement. efforts to prevent corruption from an early age, one of the methods used is Applied Neuroscience, because as well as and as much as legislation if people do not have integrity and an anti-corruption attitude, corruption will always be there.